PENGARUH PROFITABILITAS, LIKUIDITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN TAHUN 2017-2019 - Orlando Boen; Tony Sudirgo (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to determine and formulate recommendations for the effect of profitability, liquidity and capital structure on firm value in manufacturing companies listed on the IDX (Indonesia Stock Exchange) in 2017-2019. Data analysis used is 70 manufacturing companies that have been selected based on purposive sampling method with a total of 210 data for three years. The data used are secondary data in the form of financial reports that end every December 31 for each period used. Data processing uses E-views version 10. The results of this study indicate that capital structure has a positive effect on firm value, while profitability and liquidity have a negative effect on firm value.